Britain's cities : geographies of division in urban Britain - Pacione, Michael (Routledge, 1997)
This is a comprehensive introduction to current processes of urban restructuring, geographies of division and contemporary conditions within the city. Combines conceptual and empirical analyses from leading researchers in the field.